Arthroscopic Suprapectoral and Open Subpectoral Biceps Tenodesis: A Comparison of Minimum Two Year Clinical Outcomes. Issue 7 (29th July 2014) - Werner, Brian C.; Evans, Cody; Holzgrefe, Russell; Lyons, Matthew Lawrence; Hart, Joseph M.; Carson, Eric W.; Diduch, David R.; Miller, Mark D.; Brockmeier, Stephen F.
Objectives: While a vast body of literature exists describing biceps tenodesis techniques and evaluating the biomechanical aspects of tenodesis locations or various implants, little literature presents useful clinical outcomes to guide surgeons in their decision to perform a particular method of tenodesis. The goal of this study is to compare the clinical outcomes of open subpectoral biceps tenodesis and arthroscopic suprapectoral tenodesis. Our null hypothesis is that both methods yield satisfactory results with regards to shoulder and biceps function, postoperative shoulder scores, pain relief and complications. Methods: Retrospective cohort study. Patients who underwent either arthroscopic suprapectoral or open subpectoral biceps tenodesis for superior labral or long head biceps pathology with a minimum follow-up of 2 years were included in the study. Patients were excluded if they underwent significant additional shoulder procedures, including rotator cuff repair or procedures to address glenohumeral instability, if there was significant pre-operative range of motion deficits due to frozen shoulder or glenohumeral arthritis, or if they had significant contralateral shoulder pathology or surgery. Subjects were evaluated with several clinical outcome measures and physical examination including range of motion and strength. Range of motion and strength measurements were normalized to the asymptomatic contralateral limb. Power analysis indicated that a minimum of 17 subjects were required in each group (34 total) to determine a clinically meaningful difference in the outcome measures. Results: Between 2007 and 2011, 79 patients met all inclusion and exclusion criteria, which included 30 arthroscopic suprapectoral tenodesis (ASPBT) patients and 49 open subpectoral biceps tenodesis (OSPBT) patients. 23 of 30 (76.7%) ASPBT and 28 of 49 (57.1%) OSPBT patients completed clinical follow-up at an average of 3.1 year postoperative (range 2.2 - 4.3 years). The cohorts were similar in terms of age, gender, BMI, smoking and workers compensation status. Overall outcomes for both procedures were satisfactory. No significant differences were noted in post-operative Constant Murley (ASPBT: 89, OSPBT: 92, p = 0.567), ASES (ASPBT: 89, OSPBT: 88, p = 0.845), SANE (ASPBT: 86, OSPBT: 86, p = 0.982), SST (ASPBT: 10, OSPBT: 10, p = 0.597), LHB Score (ASPBT: 91, OSPBT: 94, p = 0.329), or VR-36 (ASPBT: 80, OSPBT: 79, p = 0.833). No significant range of motion or strength differences (expressed as percent of asymptomatic contralateral limb) were noted between procedures. (Table I). Conclusion: Arthroscopic suprapectoral and open subpectoral biceps tenodesis both yield excellent clinical and functional results for the management of isolated superior labrum or long head biceps pathology. No significant differences in clinical outcomes as determined by several validated outcomes measures were found between the two tenodesis methods, nor were any range of motion or strength deficits noted at minimum two-years post-operatively.